Resistance and Romans 13 in Samuel Rutherford's Lex, Rex - McAnnally-Linz, Ryan (Scottish journal of theology, 2013)
The many conflicts around the reformation of religion in the sixteenth and seventeenth centuries drew the problem of political resistance to the forefront of European political thought. Thinkers in all of the various religious camps considered scripture to be politically normative. Consequently, both pro- and anti-resistance thinkers from a variety of traditions had to engage with Romans 13:1–7, Paul's apparently definitive pronouncement in favour of obedience and, therefore, against resistance. The opponents of resistance could cite Romans 13 with fairly little explanation, but the resisters and revolutionaries faced the challenge of working with the text to draw different political conclusions from it without violating the ‘literal’ sense that they almost universally held to be authoritative. Some even aimed to bring Paul forward as a staunch supporter of the sort of violent political resistance they advocated.Lex, Rex, the political tract of seventeenth-century Scottish theologian Samuel Rutherford (1600–1661), represents a particularly comprehensive early modern justification for violent resistance against a political sovereign. Rutherford was a member of the party of the radical covenanters, who vehemently opposed the church reforms of Charles I and, when hostilities began, fervently supported the war against the king. This article explores the series of arguments, distinctions and theological moves that Rutherford employs to incorporate Romans 13 as a central supporting text for his pro-resistance argument. Among these are: the distinction between God's immediate institution of governmental power and the constitution of particular governments mediately through the people, the positing of a conditional covenant agreed upon at the constitution of any government, the scholastic distinction between voluntas beneplaciti and voluntas signi in the divine will, and the distinction between the royal office in abstracto and its concrete occupant. Using these and other arguments and distinctions, Rutherford constructs a conceptual apparatus that is able, to a great extent, to appropriate Paul's exhortation to obedience in the service of a justification of resistance. In so doing, Rutherford illustrates some of the array of theological and philosophical resources that early modern resistance theorists could marshal in support of their cause, while still maintaining their fundamental theological commitments.